Crystal structure of an inorganic pyrophosphatase from Chlamydia trachomatis D/UW‐3/Cx. Issue 3 (28th February 2022) - Maddy, Jasmine; Staker, Bart L.; Subramanian, Sandhya; Abendroth, Jan; Edwards, Thomas E.; Myler, Peter J.; Hybiske, Kevin; Asojo, Oluwatoyin A.
Abstract : Chlamydia trachomatis is the leading cause of bacterial sexually transmitted infections. C. trachomatis inorganic pyrophosphatase (CtPPase) hydrolyzes inorganic pyrophosphate during metabolism. A 2.2 Å resolution X‐ray structure of CtPPase reveals shared structural features that may facilitate the repurposing of inhibitors identified for bacterial inorganic pyrophosphatases as starting points for new therapeutics. Abstract : Chlamydia trachomatis is the leading cause of bacterial sexually transmitted infections globally and is one of the most commonly reported infections in the United States. There is a need to develop new therapeutics due to drug resistance and the failure of current treatments to clear persistent infections. Structures of potential C. trachomatis rational drug‐discovery targets, including C. trachomatis inorganic pyrophosphatase ( Ct PPase), have been determined by the Seattle Structural Genomics Center for Infectious Disease. Inorganic pyrophosphatase hydrolyzes inorganic pyrophosphate during metabolism. Furthermore, bacterial inorganic pyrophosphatases have shown promise for therapeutic discovery. Here, a 2.2 Å resolution X‐ray structure of Ct PPase is reported. The crystal structure of Ct PPase reveals shared structural features that may facilitate the repurposing of inhibitors identified for bacterial inorganic pyrophosphatases as starting points for new therapeutics for C. trachomatis.